Effect of Different Hydrophilic Polysaccharide Colloids on the Oil of Fried Chicken Nuggets Influence of Permeation - Xiaoping FENG; Yumei LIU; Tianyou WU; Shuangli XIONG (Shipin gongye ke-ji, 2024)
In order to investigate the effect of different hydrophilic polysaccharide colloids on the reduction of oil content and oil penetration of fried chicken nuggets, five hydrophilic polysaccharide colloids (carrageenan, xanthan gum, guar gum, sodium alginate, carboxymethyl cellulose) were added to the coating batter of fried chicken nuggets at the concentrations of 0.2%, 0.4%, 0.6%, 0.8% and 1.0% respectively, and the coating battering rate of the chicken nuggets, oil content and moisture content of the crust and nuggets were determined for each treatment group by determining the optimal addition amount of the five hydrophilic polysaccharide colloids. By determining the coating rate, oil and moisture content of chicken meat nuggets in each group, and taking the oil content of crust as the evaluation index, the optimal addition amount of five hydrophilic polysaccharide colloids for oil reduction was screened out, and the effects of texture, sensory quality, surface hydrophobicity, fluorescence intensity and oil migration were investigated in each treatment group under the optimal addition amount. The results showed that the 1% carboxymethyl cellulose group had the lowest oil content in the crust of fried chicken nuggets, the highest elasticity and sensory elasticity, and the best sensory score. Compared with the control group, the sulfhydryl content was significantly lower (P<0.05), the disulfide bond content was significantly higher (P<0.05), and the surface hydrophobicity index (H0) and the λmax of the emission wavelength of fluorescence intensity were increased in all treatment groups. Compared with the control and other treatment groups, 1.0% carboxymethyl cellulose and 0.2% xanthan gum groups had lower sulfhydryl content, higher disulfide bonding content, H0 and fluorescence intensity, lower surface oil content, less oil penetration during Sudan red staining process, and better inhibition of oil penetration of fried chicken nuggets. In conclusion, this study would provide the theoretical basis for low-fat and healthy high-quality fried chicken nuggets, and had a broad application prospect in the field of healthy fried meat products.